EDUCATIONAL TRANSFORMATION: FROM BOARDING SCHOOL TO PESANTREN WITH BI'AH ARABIYYAH - Wiza Novia Rahmi; Asti Nazhyfa; Yasmadi; Rahmawati (Al-Masail: Journal of Islamic Studies, 2024)
This research focuses on revealing the forms and management of Arabic language culture, known as "bi’ah ‘arabiyyah," at the Modern Diniyyah Islamic Boarding School (PPMD) Pasia through various boarding programs. The research methodology employed is a qualitative approach with a case study framework. The data analysis process involves four main stages: data collection, data reduction, data display, and data realization. The findings of this study uncover that an effective strategy for shaping bi’ah ‘arabiyyah at PPMD Pasia is manifested through the diversity of boarding programs. These programs encompass Arabic language days, bi-weekly muhaddatsah activities, morning mufradat sessions, and the presence of a conducive environment for reading and the Arabic Club. The varied boarding programs positively contribute to the formation of high-quality bi’ah ‘arabiyyah. Consequently, their impact is felt in the enhancement of the quality of learning activities within the classrooms. The significance of diverse boarding programs as a means of cultivating a positive bi’ah ‘arabiyyah becomes a crucial point throughout the entire research. The successful implementation of these programs creates a conducive environment for the development of Arabic language proficiency among the students. Therefore, this research provides a clear depiction of the role of boarding programs in shaping bi’ah ‘arabiyyah and fostering an optimal learning atmosphere at PPMD Pasia